Deficiency of cysteinyl cathepsin K suppresses the development of experimental intimal hyperplasia in response to chronic stress. Issue 8 (August 2020) - Meng, Xiangkun; Piao, Limei; Wang, Hailong; Inoue, Aiko; Huang, Zhe; Jiang, Haiying; Nakamura, Kae; Sasaki, Takeshi; Li, Xiang; Xu, Wenhu; Yu, Chenglin; Hu, Lina; et al.
Abstract : Background: Chronic psychological stress (CPS) is linked to cardiovascular disease initiation and progression. Given that cysteinyl cathepsin K (CatK) participates in vascular remodeling and atherosclerotic plaque growth in several animal models, we investigated the role of CatK in the development of experimental neointimal hyperplasia in response to chronic stress. Methods and results: At first, male wild-type (CatK +/+ ) mice that underwent carotid ligation injury were subjected to chronic immobilization stress. On postoperative and stressed day 14, the results demonstrated that stress accelerated injury-induced neointima hyperplasia. On day 4, stressed mice showed following: increased levels of monocyte chemoattractant protein-1, gp91phox, toll-like receptor-2 (TLR2), TLR4, and CatK mRNAs or/and proteins, oxidative stress production, aorta-derived smooth muscle cell (SMC) migration, and macrophage infiltration as well as targeted intracellular proliferating-related molecules. Stressed mice showed increased matrix metalloproteinase-2 (MMP-2) and MMP-9 mRNA expressions and activities and elastin disruption in the injured carotid arteries. Second, CatK +/+ and CatK deficiency (CatK −/− ) mice received ligation injury and stress to explore the role of CatK. The stress-induced harmful changes were prevented by CatK −/− . Finally, CatK +/+ mice that had undergone ligation surgery were randomly assigned to one of two groups and administered vehicle or CatK inhibitor for 14 days. Pharmacological CatK intervention produced a vascular benefit. Conclusion: These data indicate that CatK deletion protects against the development of experimental neointimal hyperplasia via the attenuation of inflammatory overaction, oxidative stress production, and VSMC proliferation, suggesting that CatK is a novel therapeutic target for the management of CPS-related restenosis after intravascular intervention therapies. Abstract : Supplemental Digital Content is available in the text